VAST-Agro A community-based vulnerability and adaptive capacity assessment methodology for various agroecosystem - Wagan, Amparo M. (Transactions of the National Academy of Science and Technology, 2011)
Vulnerability and adaptive capacity assessment is a necessary step prior to planning, implementation and prioritization of responses to changing climate. Often results of global and regional assessments for a more focused and realistic adaptation measures, particularly for the agriculture sector, which is not highlighted in any of the available hazard assessment procedures. This paper aims to present a structured approach to vulnerability assessment specific for the Philippine agricultural systems at the local level. Available hazard assessment procedures were reviewed and examined in terms of their purpose, framework, methods, agriculture-related data and applicability to agriculture areas facing climate change. Based on the concept that vulnerability to climate change is the interaction of exposure to climate change-related hazards and their potential impacts as determined by sensitivity and adaptive capacity, a stepwise procedure was designed for understanding the local situation, describing the climate-related hazards, describing vulnerabilities, capacities and local adaptation measures. Climate-related and agriculture indicators were identified to describe exposure of the production systems and the farming communities to hazards, sensitivity of the system and groups, preparedness and adaptive capacity of the farming communities including physical, economic and technological adaptation capacities. As a community-led vulnerability assessment, an instrument was devised requiring data collection techniques involving community participation as well as integration of science, technical and local knowledge. A test of the methodology in the upland areas provided outputs including maps of vulnerability index that showed areas requiring immediate attention and specific adaptation measures needed.